Artistic expression in the drawings of middle school students and its relationship to the sex variable (Journal of the College of Basic Education, 2022)
The research aimed in identifying the styles of art expression in paintings of preparatory school students with the similarity and difference in the art expression according to sexual variable. This search was done on the two samples of students of the prepare ory-school from(16) age from both sexes the first sample was used for the exploratory research . there were (180) students, (90) boys and (90) girls, who were taken from two schools, also this sample was used in the proving and affixing the research tool . the students of the second research were (400) students in the range of (200) boys and (200) girl, who were taken from(8) preparatory – school in Baghdad/ AL-resift. Only one tool was used in this research, this tools is (selection tool for style art- expression), which has done by (homady,1998). Also it was designed to limit the styles of art – expression in the pointing of secondary stage, which it was used here in this research according to what (victor Linfield) and (Herbert Reid) con clued that these styles visual-sensory which could be seen from overdue childhood on ward; of what encouraged the research of use it in this research of tar becoming sure it is true. The current research researched to finding of two distant styles in the in paintings of the students of preparatory – school (16) years – these difference between these two styles were he a statistic sign at level (0,05) which were (visual style) and (subjective) also two mixed distinct styles showed from each other which are completely visual / completely subjective, and completely subjective/ visual- subjective there fore the research saw to combine each one the closest point to it so it became only two visual and subjective. Also there is no repetitions of difference between the style of the painting of the boys and girls is with statistic indication at level (0,05) which is proving that the two styles are not distinct in this scope. Also the normative wrong was calculated for quadruple connection which shows that it is smaller then connection element art – which is not a meaning sing which arranged no finding of relation between the styles of art – expression and sexual variable . In the light or results of this research the research introduced suitable recommend nations and suggestion to do another research concerning field connected with this important studying stage which they believe that it supports the role and the importance of the art education.